The impact of parental knowledge about selecting and caring for glasses on compliance with glasses use in children who use gadgets at Methodist Elementary School–9 Fields - Nainggolan, Roy Candra; Zulianti, Zulianti; Irma, Khairuna; Romadhon, Syahru (Institute of Computer Science (IOCS), 2025)
The use of glasses in children requires supervision because children tend to be disobedient to use glasses routinely and even take off their glasses. This happens for various reasons, namely children feel uncomfortable, other friends' bad views of glasses users and are not confident in their appearance. The results of the study stated that parental knowledge was at the analysis level and was good, seen from more than 60 parents who gave good responses regarding the statement and the level of child compliance was at the level of trust seen from the answers to the results of the data analysis which stated that there was an impact of knowledge on compliance with glasses use.